(3GdeNJGQ ef TYQ GdHMJQjs - (3eLghds; (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s
(3ChdgG (B:s
(3ef bUjOI jeOM HgG CHG SYjO eMeO Hf jhSa GdKZQj(B: (3RYe GdZQGH efHF GdCfHGA Cf GdCMHI BPfhG HnKfGpA s
(3BNQgG (B:s
(3JXf GdHQb eYJQVG EPG eG LdG Yf KZQgG MSf GHJSGpe cfhpQ GdG bMhGf LdGg Wd hSeW GdOQ aUd aj GdfXGpe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B26 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B779s
Keywords: (3GdCOHs